DIGITAL LITERACY ANALYSIS OF CORPORATE SOCIAL RESPONSIBILITY CONDUCTED BY PT OLAHKARSA INOVASI INDONESIA - safira, ira; Anggraini, Choiria (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Pembangunan Nasional Veteran Jakarta, 2023)
Literacy is an important part of CSR implementation. If the company is literate, the company can improve the quality of its company using strategies related to CSR. PT Olahkarsa Inovasi Indonesia in seeing this phenomenon tries to carry out literacy on the concept of CSR in Indonesia with digital content. Researchers, in this case, conducted research using qualitative methods with data collection techniques through interviews and observations with the aim of knowing the public communication model and information literacy model used by PT Olahkarsa Innovation Indonesia. The limits and scope of communication and literacy in this study regarding CSR is the digital literacy that has been done by the subject. This research refers to two theories, namely Aristotle's Rhetoric and THE SCONUL theory. This study aims to determine the process carried out by PT Olahkarsa Inovasi Indonesia to direct companies in sustainable CSR implementation.